Industrial tourism as an effective direction of urban regeneration (analysis of Kryvyi Rih practice) - Patsiuk, Viktoriia; Kazakov, Volodymyr (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Formulation of the problem. The world is constantly moving towards the post-industrial phase of development of society, and if the majority of civilized Western countries have decided on their place and role, the cities of Ukraine are just beginning to outline their future landmarks. This is especially true for the future of single-industry cities, the number of which in Ukraine is quite large. Kryvyi Rih is the largest city with exclusively industrial specialization, performing administrative functions only at the local level and having a scientific sector almost completely focused on the needs of the industrial complex. For the last 10 years, managers and scientists have been actively thinking about the problem of diversifying the city’s economy and changing its image, and this is reflected in the Marketing Strategy for the city development. Industrial tourism is one of the key tasks of the Strategy. The promising character of the chosen direction of activities is confirmed by the practice of European countries, which are guidelines for development for us. This is due to the fact that not only individual cities, but also entire regions of Great Britain, Germany, France, Poland, the Czech Republic have a wide experience in regeneration of former industrial territories and further popularization of successful practices through industrial tourism. Methods. The research is based on the system approach and the dialectical method of cognition. The key scientific results are obtained using a complex of general scientific methods, namely: analysis and synthesis, abstraction, theoretical generalization. The historical method enables determining significant moments for development of this tourist destination. With the help of these methods, industrial tourism is considered in its internal and external relations entirety. The simulation method enables presenting the organizational model of this tourist destination at the local level. Comparative-geographical and statistical analysis methods allow assessment of the state and dynamics of tourism development in Kryvorizhzhia (Kryvyi Rih region). Based on the method of observation and analysis, the most visited objects of industrial tourism in Kryvyi Rih are systematized and their base map is created. The study aims to analyze best practices of implementing theoretical developments concerning establishment of industrial tourism in Kryvorizhzhia so that Ukrainian cities with similar resources can factor in all positive areas and minimize shortcomings. Results. The theoretical foundations of industrial tourism establishment are analyzed and this definition is outlined. The practice of Kryvyi Rih concerning integrated development of industrial tourism as a direction of further regeneration of the city, which is pioneering for our country, is revealed, the results obtained are analyzed and available shortcomings are identified. Scientific novelty and practical significance. An organizational model of industrial tourism has been developed, which demonstrates the relationship between the resource of the territory and the management mechanism for introducing tourist activities in order to create a tourist product and bring it to the tourist.